Admission plasma glucose levels within the normal to mildly impaired range and the outcome of patients with acute coronary syndrome. Issue 8 (December 2017) - Buturlin, Kirill; Minha, Saar; Rozenbaum, Zach; Neuman, Yoram; Shlezinger, Meital; Goldenberg, Ilan; Mosseri, Morris; Pereg, David
Background: Elevated admission plasma glucose levels >140 mg/dl are associated with adverse clinical outcomes in both diabetic and non-diabetic patients admitted with acute coronary syndrome (ACS). We aimed to evaluate the association between admission plasma glucose levels <140 mg/dl and the outcome of non-diabetic patients admitted with acute coronary syndrome. Methods: The study population consisted of patients with acute coronary syndrome included in the Acute Coronary Syndrome Israeli Survey during 2000–2013. Diabetic patients were excluded. The primary endpoint was all-cause mortality at one year. Results: The 452 0 patients had a mean age of 61.7±13.5 years and were stratified into four quartiles according to admission plasma glucose (60–94, 95–105, 106–119, 120–140 mg/dl). Patients with higher admission plasma glucose were older and included a higher percentage of smokers. In addition, the higher the glucose so also did they have a poorer risk factor profile including a higher body mass index, total and low-density lipoprotein cholesterol and triglyceride levels, and lower high-density lipoprotein cholesterol levels. During the first year 5.2% of patients died. A comparison of one-year mortality according to admission plasma glucose quartiles demonstrated a significant and progressive increase in mortality risk as admission plasma glucose rose (3.5%, 4.1%, 6.1%, 6.4%, respectively, p =0.001). However, this association lost its clinical significance following a multivariate analysis ( p =0.08). Conclusions: High admission plasma glucose levels within the normal to mildly impaired range are associated with increased one-year mortality in non-diabetic acute coronary syndrome patients. However, the higher glucose level is probably not the cause for the adverse outcome but rather a marker for high risk. Our findings support the definition of 140 mg/dl as the cutoff for clinically acceptable admission glucose levels in patients with acute coronary syndrome.